ANALISIS KEMAMPUAN PEMAHAMAN GRAFIK KINEMATIKA SISWA SEKOLAH MENENGAH ATAS - Surya Gumilar (Universitas Sultan Ageng Tirtayasa, 2015)
This research is aimed to know understanding graph of kinematic student with using Criteria Respon Index (CRI). The kind of research is descriptive research that described and interpretated object as the real condition. Understanding of student about graph of kinematic is showed in knowing concept, misconception, and unknowing concept that is measured by multiple choice objective test using Test of Understanding Graph of Kinematics (Tugk). The result of this research shows that understanding graph of kinematic student is low. It is known by looking test score that is gotten by student in every unit analysis test.